Study on impact forces of the underwater cavity projectile - Dung, Nguyen Thai; Thuyen, Nguyen Duc (Vietnam Journal of Science and Technology, 2016)
The motion of the underwater projectile with cavity effect including two motions: the projectile moves in the forward direction, center of mass of the projectile rotation around its nose makes tail of the projectile impacts on the cavity wall. According to, the impact forces occur, they include the drag force at its none, the impact force at impact point. The paper studies the forces occur on during motion of the underwater cavity projectile. Added, this paper considers the effect of the length and distributive projectile to the magnitude of impact force and the drag force of the underwater cavity projectile.